A Review on the Present Scenario of Air Quality Associated with Indian Mining Operations - Yadav A.K.; Jamal A. (My University, 2025)
Compositional changes to air quality from coal mining are not only the most visible impact from these activities on the environment, they can also immediately affect the health of mine professionals and adjoining populations. The presence of gases and suspended solids emitted by mining activities affects the human respiratory system and decreases production in mines. This article summarizes a case study of several Northern Coalfields Limited (NCL) coal mines with an emphasis on particulate matter (PM) to report the status of air quality connected to coal production and overburden removal. The concentrations of sulfur dioxide (SO2), nitrogen oxides (NOx), and suspended particulate matter (SPM) reported in the literature are also summarized in table form to allow comparisons to the permissible standards set by the Indian Central Pollution Control Board (CPCB) and other standards used around the world. An up-to-date status of air quality at coal mines is compared for mines located in different parts of India. Subsequently, all coal mines were divided into different classes in regard to the severity of their emissions. These classes are, in increasing order of severity, green, yellow, red, and black. SPM measurements were tabulated in regard to concentration and composition. Our article concludes with the recommendation that an environmental impact assessment (EIA) to be conducted to better characterize changes in the environment from mining emissions to develop integrated mitigation measures and to identify additional parameters to define air quality at mines. © 2016 Wiley Periodicals, Inc.